2022
DOI: 10.3390/cancers14204997
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Immunological Profiles in NSD3-Amplified LUSC through Integrative Multi-Scale Analyses

Abstract: The histone H3 lysine 36 (H3K36) methyltransferase NSD3, a neighboring gene of FGFR1, has been identified as a critical genetic driver of lung squamous cell carcinoma (LUSC). However, the molecular characteristics, especially the immunological roles of NSD3 in driving carcinogenesis, are poorly understood. In this study, we systematically integrated multi-omics data (e.g., genome, transcriptome, proteome, and TMA array) to dissect the immunological profiles in NSD3-amplified LUSC. Next, pharmaco-transcriptomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 60 publications
3
3
0
Order By: Relevance
“…Later, two studies reported the discovery and characterization of NSD3 PROTAC, being more efficient in blocking NSD3 function and decreasing Myc oncogenic node. Both PROTAC were synthesized incorporating an NSD3-PWWP antagonist link to an E3 ligase, showing the degradation of both NSD3 isoforms in cell lines of AML, multiple myeloma and lung cancer [64,85]. These studies correlate with our findings that NSD3S/MYC interaction stabilizes and activates MYC transcriptional activity.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Later, two studies reported the discovery and characterization of NSD3 PROTAC, being more efficient in blocking NSD3 function and decreasing Myc oncogenic node. Both PROTAC were synthesized incorporating an NSD3-PWWP antagonist link to an E3 ligase, showing the degradation of both NSD3 isoforms in cell lines of AML, multiple myeloma and lung cancer [64,85]. These studies correlate with our findings that NSD3S/MYC interaction stabilizes and activates MYC transcriptional activity.…”
Section: Discussionsupporting
confidence: 81%
“…It is accepted that innate and adaptive immunity plays important roles in tumor immune surveillance. Amplification of NSD3 in patients with LUSC exhibits a decrease in type II IFN response, leading to an immune-desert pro-tumorigenic phenotype [64]. In breast cancer, increased expression of NSD3 correlated with a decrease CD8+ T cells and increased PD-L1 gene [65], in agreement with Xu et al in lung cancer.…”
Section: Ifn Pathwaysupporting
confidence: 79%
“…Transcriptomic data from immunotherapy-treated human renal cell carcinoma have been previously reported. 21 Data set from metastatic melanoma treated with checkpoint blockade immunotherapy were downloaded from https://ddbj.nig.ac.jp/resource/bioproject/PRJEB23709 .…”
Section: Methodsmentioning
confidence: 99%
“…The information on the 122 immunomodulators (MHC, immune receptors, chemokines, and immune stimulators) and 33 well-known effector genes of tumor-infiltrating immune cells was according to previous studies. 21 , 22 , 23 Gene signatures of 29 immune cell types and immune-related pathways were based on the previous study. 24 Exhausted and cytotoxic T-cell signatures were scored as the sum of the corresponding gene sets (exhausted: TIGIT, HAVCR2, CTLA4, LAG3, and PDCD1; cytotoxic: GZMA, GZMB, GZMK, IFNG, and IL2).…”
Section: Methodsmentioning
confidence: 99%
“…By utilizing multi-scale analyses (genome, transcriptome, proteome, and TMA array), ref. [ 2 ] provides the first evidence that NSD3 gene amplification defines a non-immunogenic phenotype in LUSC and is associated with poor immunotherapy outcomes. Additionally, the authors demonstrate that high unfolded protein response (UPR) promotes the “cold” tumor immune microenvironment of NSD3-amplified LUSC.…”
mentioning
confidence: 99%